Risk vs Reward Strategies in Indirect Presidential Elections: Political Parties and the Selection of Presidential Electors in Germany, 1949–2017. Issue 4 (2nd October 2019) - Köker, Philipp
Abstract : Parties across parliamentary republics compete fiercely over capturing the presidential office. However, they are often torn between seeing their preferred candidate elected and exploiting the election for publicity purposes. The German case, specifically parties' ability to nominate extra-parliamentarian electors (EPEs) as part of the electoral college, offers a particularly interesting perspective on how parties balance these competing goals. While EPEs allow parties to boost their profile and strengthen ties with selected groups, they also present a risk factor as their voting behaviour is more difficult to predict. Based on a novel data set on party delegations in German presidential elections, 1949–2017, the analysis shows that – contrary to traditional assumptions – competition in the electoral college did not play a role in EPE nominations. Rather, party strategies were influenced by the varying signalling power of the elections. Parties were more risk-averse and nominated fewer EPEs during grand coalitions, when they were part of the federal government, or when federal elections approached, yet nominated more EPEs when they had a larger support base to reward. The results call for further comparative research on indirect elections and different types of EPEs in Germany.